2022
DOI: 10.3390/curroncol29060324
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Malignancy in Giant Cell Tumor: A Single-Center Study

Abstract: Giant cell tumor of bone (GCTB) undergoes a sarcomatous transformation. Secondary malignancy in giant cell tumor (MGCT) is associated with radiotherapy and has a dismal prognosis. We reviewed medical records to investigate the clinicopathological characteristics and prognosis of MGCT patients. The enrollment criterion was high-grade spindle-cell sarcoma, which developed at the site of prior GCTB treatment. Twelve patients were analyzed: six females and six males. The median age was 42.5 years. Benign recurrenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…In this study, en bloc resection was performed for tumors with large extraosseous lesions, pathologic fractures with joint involvement, complex fractures, or dispensable bones, such as the proximal fibula and distal ulna. The local recurrence rate (41.4%), distant metastasis rate (34.5%), malignant transformation rate (6.9%), and mortality rate (6.9%) after reoperation for local recurrence after en bloc resection were higher than those reported in previous studies (local recurrence rate after initial surgery (median), 20% [ 2 ]; distant metastasis rate, 1–9% [ 3 , 4 , 5 , 6 , 7 , 8 ]; malignant transformation rate (median), 2.4% [ 9 , 10 ] and mortality rate, 1–1.7%) [ 11 , 12 , 13 , 14 ]. Therefore, recurrent GCTB after en bloc resection seems to exhibit markedly aggressive behavior and warrants careful follow-up after reoperation ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In this study, en bloc resection was performed for tumors with large extraosseous lesions, pathologic fractures with joint involvement, complex fractures, or dispensable bones, such as the proximal fibula and distal ulna. The local recurrence rate (41.4%), distant metastasis rate (34.5%), malignant transformation rate (6.9%), and mortality rate (6.9%) after reoperation for local recurrence after en bloc resection were higher than those reported in previous studies (local recurrence rate after initial surgery (median), 20% [ 2 ]; distant metastasis rate, 1–9% [ 3 , 4 , 5 , 6 , 7 , 8 ]; malignant transformation rate (median), 2.4% [ 9 , 10 ] and mortality rate, 1–1.7%) [ 11 , 12 , 13 , 14 ]. Therefore, recurrent GCTB after en bloc resection seems to exhibit markedly aggressive behavior and warrants careful follow-up after reoperation ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 83%
“…GCTB have a high local recurrence rate (median, 20%) [ 2 ], 1–9% of GCTBs develop distant metastases [ 3 , 4 , 5 , 6 , 7 , 8 ], and approximately 2.4% of GCTBs develop malignant transformation (secondary malignant GCTB) [ 9 , 10 ]. The prognosis of malignant GCTB remains poor, with a reported mortality rate of 42–70% [ 11 , 12 , 13 , 14 ]. Curettage is the mainstay of treatment for preserving good limb function; however, it is associated with a relatively high local recurrence rate (median, 20%) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patel et al reported five cases in the phalanges and advocated that the high risk of recurrence was related to the difficulty to eradicate the tumor in the hand because of the complex arrangements of soft tissues in the hand and suggested amputation or ray resection if the cortical integrity was compromised (13). Depalmaet al found 100% success rate when the tumor was completely excised and either the joint was fused or replaced by a bone graft (8).…”
Section: Discussionmentioning
confidence: 99%
“…Giant cell tumor (GCT) of bone is a relatively common, benign but aggressive tumor and usually involves the metaphyseal-epiphyseal region of long bones, usually at the distal femur and proximal tibia (8). GCTs are typically seen in early adulthood with a peak incidence between 30 and 50 years (10).…”
Section: Introductionmentioning
confidence: 99%